DNase Treatment Prevents Cerebrospinal Fluid Block in Early Experimental Pneumococcal Meningitis. Issue 4 (23rd August 2021) - Pavan, Chiara; L. R. Xavier, Anna; Ramos, Marta; Fisher, Jane; Kritsilis, Marios; Linder, Adam; Bentzer, Peter; Nedergaard, Maiken; Lundgaard, Iben
Abstract : Objective: Streptococcus pneumoniae is the most common cause of bacterial meningitis, a disease that, despite treatment with antibiotics, still is associated with high mortality and morbidity worldwide. Diffuse brain swelling is a leading cause of morbidity in S pneumoniae meningitis. We hypothesized that neutrophil extracellular traps (NETs) disrupt cerebrospinal fluid (CSF) transport by the glymphatic system and contribute to edema formation in S pneumoniae meningitis. Methods: We used DNase I treatment to disrupt NETs and then assessed glymphatic function by cisterna magna injections of CSF tracers in a rat model of S pneumoniae meningitis. Results: Our analysis showed that CSF influx into the brain parenchyma, as well as CSF drainage to the cervical lymph nodes, was significantly reduced in the rat model of S pneumoniae meningitis. Degrading NETs by DNase treatment restored glymphatic transport and eliminated the increase in brain weight in the rats. In contrast, first‐line antibiotic treatment had no such effect on restoring fluid dynamics. Interpretation: This study suggests that CSF accumulation is responsible for cerebral edema formation and identifies the glymphatic system and NETs as possible new treatment targets in S pneumoniae meningitis. ANN NEUROL 2021;90:653–669